Franch-Canadian Communities in the American Upper Midwest during the Nineteenth Century - McQuillan, D. (Cahiers de géographie du Québec, 1979)
The pattern of nineteenth-century French-Canadian settlements in the American Midwest bore no relation to the pattern of fur-trading posts of the eighteenth century. French-Canadians of the nine-teenth century were attracted by employment opportunities along the farming, lumbering, and mining frontiers. Detroit, Chicago, and Minneapolis-St. Paul developed French-Canadian parishes which maintained links with rural communities. Survival of the French language, cultural heritage, and affiliation with the Catholic Church varied throughout the region. Americanization of French-Canadians went hand in hand with their commercial success. A French-Canadian identity survived in the poorest, marginal, rural areas of northern Michigan, Wisconsin, and Minnesota.